Development of Fiqan as a Media for Fiqh Learning for Class X MA Mambaul Ulum Megaluh Students - Zainul Qowim; Rohmat Hidayat; Mochammad Syafiuddin Shobirin (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to develop an animated video-based learning media in the subject of Fiqh class X MA Mambaul Ulum Megaluh. Products can be used as interesting teaching materials according to the needs of students. This research is a development research (R&D) using the ADDIE development procedure. This development model is divided into five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. Data obtained through observation, interviews and questionnaires. Product validation was carried out by media expert lecturers and material experts who stated that the media was suitable for use in field trials with revisions according to suggestions, and questionnaire responses from students with the conclusion that the researchers took that the criteria for learning media were interesting, so that the learning media that had been developed by the researchers were feasible. to be used as a support for the learning process.